Leadless Cardiac Pacemakers: Pacing Paradigm Change - Neuzil, Petr; Reddy, Vivek Y (Current cardiology reports, 2015)
Traditional transvenous approach for permanent cardiac pacing can be associated with significant acute and chronic complications related partly to either the insertion of transvenous lead or subcutaneous placement of pacemaker device. We summarize the current status of a novel self-contained leadless cardiac pacemaker in the first-in-human and subsequent series of feasibility studies in patients indicated for ventricular rate-responsive pacing (VVI). Using a femoral venous approach, the device is implanted at the right ventricular apical septum region. We describe the technical and clinical characterization of this innovative technology. Two different systems of leadless pacemakers are currently implanted to the patients. Up to now, the electrical parameters, such as pacing thresholds, sensing parameters, and pacing impedances, either improved or remained stable within the accepted range. In this chapter, we also discuss the potential benefit for the future, but in summary, all available data demonstrate the feasibility of leadless cardiac pacing.
Keywords: Pacemaker, Artificial; implantované elektrody; Cardiac Pacing, Artificial; Equipment Design; kardiostimulátor; lidé; kardiostimulace umělá; studie proveditelnosti; Feasibility Studies; design vybavení; Electrodes, Implanted; Treatment Outcome; výsledek terapie; srdeční arytmie; Arrhythmias, Cardiac; Humans